Sistem Informasi Penampil Pengumuman Fakultas Teknik Universitas Diponegoro - Fajar Yogi Hernawan (Jurnal Informatika Upgris, 2016)
Abstract - Engineering Faculty is the biggest faculty with the highest number of departements and students in the Diponegoro University. The idea made SIPP (System Information Viewer Announcements Faculty of Engineering, University of Diponegoro) appears is to help disseminate information and stories of pride born from Engineering Faculty to become the impetus and motivation for more achievement.SIPP maked with 5(five) stages: requirement, analysis, design, implementation, testing. SIPP is built using the programming language PHP, HTML, CSS, Bootstrap, Javascript, and MySQL database. SIPP is expected to convey information and the pride stories of the Engineering Faculty in the multimedia. The output of the SIPP is the information shown via LCD TV screen ratio of 16: 9 which blend of images, video and running text. SIPP expected to be implemented in the lobby Engineering Faculty dean and in every department in it. Users SIPP is divided into 2 (two) they are admin faculty as the main admin and admin department as sub-admin. SIPP tested with 2 (two) test that is functionality testing by black box and performance testing with performance-analyzer application. With the implementation of SIPP environment Faculty of Engineering will be an additional alternative for the community Faculty of Engineering to obtain information.Keywords - Information, SIPP, multimedia, Engineering Faculty. Intisari – Fakultas Teknik adalah fakultas dengan jumlah jurusan dan mahasiswa terbanyak di Universitas Diponegoro. Gagasan dibuatnya SIPP (Sistem Informasi Penampil Pengumuman Fakultas Teknik Universitas Diponegoro) muncul adalah untuk membantu menyebarkan informasi dan cerita kebanggaan dari Fakultas Teknik yang menjadi dorongan dan motivasi untuk lebih berprestasi. SIPP dibuat dengan 5(lima) tahap : rencana kebutuhan, analisis kebutuhan, perancangan desain, perancangan sistem, dan pengujian. SIPP dibangun menggunakan bahasa pemrograman PHP, HTML, CSS, Bootstrap, Javascript, dan basisdata MySQL. SIPP diharapkan dapat menyampaikan informasi dan cerita kebanggaan dari Fakultas Teknik dalam bentuk multimedia. Keluaran dari SIPP ditampilkan melalui LCD TV rasio 16 : 9 yang merupakan perpaduan antara gambar, video, dan teks berjalan. SIPP diharapkan dapat dipasang di lobi dekanat Fakultas Teknik dan di setiap jurusan didalamnya. Pengguna SIPP dibagi menjadi 2(dua) yaitu admin fakultas sebagai admin utama dan admin jurusan sebagai sub-admin. SIPP diuji dengan 2(dua) pengujian yaitu uji fungsionalitas dengan black box dan uji performansi dengan aplikasi perfomnce-analyzer. Dengan penerapan SIPP akan menjadi alternatif untuk warga Fakultas Teknik mendapatkan informasi.Kata kunci – informasi, SIPP, multimedia, fakultas teknik.